2019
DOI: 10.1037/dev0000731
|View full text |Cite
|
Sign up to set email alerts
|

Implications of interparental conflict for adolescents’ peer relationships: A longitudinal pathway through threat appraisals and social anxiety symptoms.

Abstract: The goal of this study was to broaden the developmental understanding of the implications of interparental conflict (IPC) and threat appraisals of conflict for adolescents’ relationships with peers. Guided by the cognitive contextual framework and evolutionary perspectives, we evaluated a developmental model in which adolescents who are exposed to IPC perceive these conflicts as threatening to their well-being or that of their family. In turn, threat appraisals of IPC increase risk that adolescents experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 79 publications
1
21
0
1
Order By: Relevance
“…We also specified the five covariates (i.e., child gender and race, household income, parent education, marital status) as predictors of Wave 2 emotional insecurity and Wave 3 psychological problems. However, consistent with previous approaches (e.g., Weymouth et al, 2019), the structural paths for the covariates are not shown in the Figures for clarity in presentation. All the predictors were meancentered prior to the creation of the two interaction terms.…”
Section: Resultssupporting
confidence: 74%
“…We also specified the five covariates (i.e., child gender and race, household income, parent education, marital status) as predictors of Wave 2 emotional insecurity and Wave 3 psychological problems. However, consistent with previous approaches (e.g., Weymouth et al, 2019), the structural paths for the covariates are not shown in the Figures for clarity in presentation. All the predictors were meancentered prior to the creation of the two interaction terms.…”
Section: Resultssupporting
confidence: 74%
“…One of the most common tests for moderation that occurred in this literature on family processes was the comparison of associations across sons and daughters. For example, in a large purposive sample of mostly two‐parent families (PROSPER data), interparental conflict during early adolescence was associated with increases in loneliness and decreases in friendship support (but not with affiliations with antisocial peers) through changes in perceived threat associated with conflict and youth's social anxiety (Weymouth et al, ). These patterns did not differ across daughters and sons.…”
Section: Complexity and Specificitymentioning
confidence: 99%
“…The effects of children's involvement in marital conflicts (both active and passive) are extensive and their effects can be direct and long term. Observed in research the sense of threat by conflicts with peers, diminished openness to their support, increased symptoms of social anxiety and a sense of loneliness as a result of observing conflicts between parents by adolescents (Weymouth, Fosco, Mak, Mayfield, LoBraico, Feinberg, 2019), can, at a later time, be a factor impairing psychosocial abilities to deal with relational difficulties. After several years of the observation of children who in their infancy passively participated in parental conflicts, researchers noticed a strong surge of aggression in 7% of a studies sample, and a weak surge of aggression in 19%, while they did not notice any in children growing up in good family environments (Jambon, Madigan, Plamondon, Jenkins, 2019).…”
Section: Strona 186mentioning
confidence: 99%